Semantic Ambiguity Resolution in Patients With Bipolar Disorder—An Event-Related Potential Study - Schneegans, Hanna; Hoenig, Klaus; Ruchsow, Martin; Spitzer, Manfred; Connemann, Bernhard J.; Kiefer, Markus (Frontiers in Psychology, 2018)
Deficits in inhibitory function are assumed to underlie psychopathology in bipolar disorder (BD), especially in states of mania. A subdomain of inhibition, semantic inhibition (SI), referring to the suppression of irrelevant word meanings, may underlie formal thought disorder, such as flight of ideas. In the present study, we investigated SI in patients with BD during semantic ambiguity resolution using behavioral and event-related potential (ERP) measures. We presented 14 patients with BD with current manic, hypomanic or mixed clinical states and 28 healthy controls sequentially with word triplets containing either a homonym (e.g., “organ”) or a comparable unambiguous word (e.g., “piano”). Participants were instructed to make a decision whether or not the target word was related to the meaning field of the first two words. The inappropriate homonym meaning had to be inhibited to correctly perform the target decision. In addition to reaction times (RT) and error rates (ER), the N400 ERP component to the target, an electrophysiological index of semantic processing, was analyzed as measure of the amount of SI that had taken place. Analyses of the behavioral data revealed that BD patients exhibited an overall worse performance in terms of RT and ER. In the ERP data, we found differences in N400 amplitude to ambiguous and unambiguous conditions over the right hemisphere in patients with BD depending on target congruence: In incongruent trials, N400 amplitude was smaller to ambiguous than to unambiguous words. In congruent trials, in contrast, N400 amplitude was larger to ambiguous than to unambiguous words. Such ERP differences between ambiguous and unambiguous words were absent in controls. We conclude that N400 amplitude differences in ambiguous and unambiguous conditions of the BD group may reflect insufficient suppression of irrelevant homonym meanings in the right hemisphere. Disturbed semantic inhibition processes might contribute to formal thought disorder in BD.